Advances in polydiacetylene development for the design of side chain groups in smart material applications – a mini review. Issue 48 (29th November 2017) - Huo, Jingpei; Deng, Qianjun; Fan, Ting; He, Guozhang; Hu, Xiaohong; Hong, Xiaxiao; Chen, Hong; Luo, Shihe; Wang, Zhaoyang; Chen, Dongchu
Abstract : This review focuses on various side chain groups based on PDAs published over the last 3 years, covering urea, melamine, ferriferous oxide and coumarin. Perspectives on the remaining challenges and future developments are also proposed. Abstract : As a kind of smart material, polydiacetylene (PDA) has a unique conjugated structure, providing a powerful tool for building the diversity of the chemical structure, applying for different sensors. This review focuses on various side chain groups based on PDAs published over the last 3 years, covering urea, melamine, ferriferous oxide and coumarin. Perspectives on the remaining challenges and future developments are also proposed.